Analisis Dampak Faktor Lingkungan Fisik, Citra Museum, dan Emosi Pengunjung terhadap Keinginan Berperilaku (Studi pada Bagian Koleksi Nonbuku Perpustakaan Nasional RI UPT Perpustakaan Proklamator Bung Karno) - Putro, Tanto A. (Jurnal Aplikasi Manajemen, 2014)
The purpose of this research is to explain whether any impact of physical environments to the museum image, visitor's emotions and behavioral intentions of the Bung Karno Museum in Blitar. Data processing by using Structural Equation Modeling (SEM) Technique. The sample of this research is 133 visitors. The result of this research shows that museum image, visitor's emotions and behavioral intentions is not signifcantly affected by design factors, however, museum image, visitor's emotions and behavioral intentions is signifcantly affected by ambient factors. Museums need to be empowered by improve the quality of the atmosphere of the museum as a way to promote the tourism industry and the local economy.